Trajectory of Digital Transformation Policy in Indonesia from 2003 to 2024: Analysis of Trends and Policy Contents - Angelica, Laura; Andiny Soenarto, Nayla; Salsabila, Nabila (Indonesian Association for Public Administration (IAPA), 2024)
Digital transformation is a necessity that requires all sectors, including the bureaucracy, to develop systems and service models that have an impact on society. In fact, the application of information technology, which is the seed of e-government, is not new in Indonesia, Presidential Instruction Number 3 of 2003 being the first step in the application of digital technology in a government system that continues to evolve. This study aims to identify the development of digital transformation policy trends over the past two decades (2003 to 2024) and analyze policy content to map topics to see the extent to which government policies on digitalization have supported digital transformation. The research method used is qualitative by analyzing policy content. The dataset obtained for this research analysis was 93 policies from four Legal Documentation and Information Network (JDIH) sites with the final result of filtering 38 policy documents which were then analyzed using QSR Nvivo 12 Pro software. The findings explain that digital transformation policies in Indonesia have experienced fluctuating developments. Although fluctuating, the development of the policies set reflects the government's efforts to play an adaptive role in responding to demands in the digital era. Then, the results of the policy content analysis show diverse, but interrelated policy topics in creating a digital ecosystem towards digital transformation efforts.